Implementasi Strategi Pembelajaran Sastra Berbasis Literasi Ekologi di Pesantren Miftahul Ulum Sumenep - Ira Fatmawati; Afiyah Nur Kayati (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Ecological literacy in literature learning specifically studies the relationship between humans and the environment to support sustainable development through literary texts. The purpose of this study is to describe the strategies and implementation of ecological literacy-based literature learning in Islamic boarding schools. The method used in this study is qualitative with an exploratory descriptive design. Data were obtained through observation, interviews, documentation studies, and focus group discussions. The basic theory used was the three dimensions of ecological literacy: (1) Cognitive, (2) Affective, and (3) Behavioral (Action). The results of the study show that the strategies and implementation of ecology literacy-based literature learning are as follows: 1) providing reading materials with themes of nature and the environment, 2) assigning tasks to compose texts with themes of the environment and nature, 3) making nature a source of learning, 4) familiarizing students with activities carried out in order to build a character that cares for the environment through daily routine activities, such as class duty, Clean Friday activities, community service, recycling plastic waste into ecobricks, 5) setting an example by the principal and teachers, 6) motivation and encouragement from the principal and teachers to students to maintain and care for environmental cleanliness, 7) the school providing adequate facilities and infrastructure, such as trash bins and hand washing stations. The implementation of eco-literacy-based literature learning, as many as 72.2% of teachers have provided Islamic ecology-oriented story texts in their learning. Eco-literacy learning can make a positive contribution to sustainable living in pesantren-based school environments to realize quality education.